2020
DOI: 10.1021/acschembio.0c00684
|View full text |Cite
|
Sign up to set email alerts
|

Combining Rational Design and Continuous Evolution on Minimalist Proteins That Target the E-box DNA Site

Abstract: Protein-based therapeutics are part of the next-generation arsenal of drugs being developed against proto-oncoprotein Myc. We designed protein MEF to mimic the basic region/helix-loop-helix/leucine zipper (bHLHZ) domain of Max and Myc, which bind to the E-box motif (enhancer box, CACGTG). To make MEF, we started with our rationally designed ME47, a hybrid of the Max basic region and E47 HLH, that effectively inhibited tumor growth in a mouse model of breast cancer. We used phage-assisted continuous evolution (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…This could be because Myc is only boosted by E-box sequences through preferential but not absolute specificity and may bind at all available promoters. , To overcome this, other Myc-inhibiting miniproteins may be explored for ApP tagging and intracellular delivery. Recently, two such proteins, dubbed MEF and Mad, have surfaced with the latter exhibiting greater inhibition of Myc-mediated transcription than Omomyc. In control studies, we observed that free Omomyc and Omomyc-E30 exhibited no inhibitory effect and negligible cytosolic delivery despite reports of Omomyc possessing intrinsic cell-penetrating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because Myc is only boosted by E-box sequences through preferential but not absolute specificity and may bind at all available promoters. , To overcome this, other Myc-inhibiting miniproteins may be explored for ApP tagging and intracellular delivery. Recently, two such proteins, dubbed MEF and Mad, have surfaced with the latter exhibiting greater inhibition of Myc-mediated transcription than Omomyc. In control studies, we observed that free Omomyc and Omomyc-E30 exhibited no inhibitory effect and negligible cytosolic delivery despite reports of Omomyc possessing intrinsic cell-penetrating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…MEF displays slightly increased E-box binding and strong cooperative binding. [74] In recent work Moellering and co-workers used the basic helix along with the minimal zipper helix from Max to target E-Box DNA with high affinity. The individual helices harbor olefin containing amino acids allowing for side-chain stapling by ring-closure-metathesis and appropriate amino acids for ligation with a maleimide linker.…”
Section: Max-derived Mini Proteinsmentioning
confidence: 99%
“…This yields MEF which they term a ‘franken‐protein’ as it is composed of domains from different classes of TFs, preventing heterodimerization. MEF displays slightly increased E‐box binding and strong cooperative binding [74] …”
Section: Targeting Of Dna With Synthetic Peptidesmentioning
confidence: 99%
“…We have used raRonal design and phage-assisted evoluRon to discover small proteins that target specific 6 base-pair (bp) DNA sequences. [1][2][3][4] Simply put, our proteins comprise modules from various transcripRon factors (TF) families that we cut-and-paste together. Our 60-90 amino-acid (aa) frankenproteins cooperaRvely bind as dimers to the 6 bp E-box sequence 5'-CACGTG with low nM binding affiniRes, without binding to nonspecific DNA controls even at micromolar concentraRons.…”
Section: Introductionmentioning
confidence: 99%